2013
DOI: 10.13080/z-a.2013.100.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strong microwave electric field radiation on: (1) vegetable seed germination and seedling growth rate

Abstract: The effect of high power microwave (HPM) irradiation on seed germination and seedlings was evaluated. Vegetable seeds were subjected to HPM irradiation. The main focus was on the thermal heating elimination during seeds irradiation. For that reason short high frequency microwave pulses were used. The study object was seeds of different harvest years (2000, 2003 and 2008) of radish (Raphanus sativus L.) variety 'Babtų žara', tomato (Lycopersicon esculentum Mill.) variety 'Viltis', carrot (Daucus sativus Rohl.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…Besides the favourable effect on seed germination, some authors detected a positive effect on seed yield. The effect of the treatment depends on the year, exposure duration and frequency, which is in accordance with the results of Radzevičius et al (2013) who also included hybrid type and geomagnetic conditions as prerequisites for the success of this presowing treatment. However, significant differences occurred in analysis of the correlation between the year of study and exposure time.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Besides the favourable effect on seed germination, some authors detected a positive effect on seed yield. The effect of the treatment depends on the year, exposure duration and frequency, which is in accordance with the results of Radzevičius et al (2013) who also included hybrid type and geomagnetic conditions as prerequisites for the success of this presowing treatment. However, significant differences occurred in analysis of the correlation between the year of study and exposure time.…”
Section: Resultssupporting
confidence: 86%
“…The effect of PEMF on soybean seed germination depended on the year (A), duration of exposure (B) and frequency (C), and year-by-duration of exposure interaction (A × B), year-by-frequency interaction (A × C) and exposure interaction-by-frequency interaction (B × C) ( Table 1). The main indicators of good seed quality are germination and vigour (Radzevičius et al, 2013). The number of plants per surface unit in field conditions is one of the major yield components (Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, a high amount of this antioxidant for human could be painful and cause adverse effect. Thus, the precise determination of ascorbic acid in various plant species or cultivars is very important [21][22][23][24][25]. There seems to be little doubt that acids and sugar not only contribute to the sweetness and sourness of tomatoes but are also major factors in overall flavour intensity.…”
Section: Tomato Biochemical Compositionmentioning
confidence: 99%
“…There is a wide variation of ascorbic acid content in different cultivars. According to Mathews, the vitamin C values for 41 cultivars ranged from 10.7 to 20.9 mg 100 g -1 (23). Ten years of data presented by a Lithuanian scientist showed that the average amount of ascorbic acid was 16.20 mg 100 g -1 in different tomato cultivars [36].…”
Section: Plants For the Futurementioning
confidence: 99%
“…Radish seeds harvested exposed to 9.3 GHz microwaves had higher germination compared with non-irradiated seeds. High power microwaves increased radish germination energy by 6% (RADZEVIČIUS [4]).…”
Section: Introductionmentioning
confidence: 99%